Medical identification in mass graves and its role in criminal evidence - جوني علي مسلم; داود صباح سامي (Journal of Legal Sciences, 2021)
Medical identification is deemed of the most important evidences in the criminal investigation on massive cemeteries, as it is identified the unknown individuals either alive or died. Whereas the victims of massive cemeteries are individuals were murdered and then buried or buried alive and thence identifying the bodies of the victims should be evaluated technically and need medical experience by checking its apparently or internally (anatomically) by expert (Forensic Medical Doctors) to make the identity of victim known, diagnosed the real cause of death and its time, making the identities of convicts known to prove their criminal responsibility for international and national crimes they made against victims. Medical Identifications is differed from case to another according to the changes may incur on the buried body, as it may made by ordinary means or by using technologies of genetic impression if the bodies are pieces, or in advanced stages of decay . Thus, medical identifications by its results of technical or material evidences has considerable importance to conclude the fact and reach the justice.